2020
DOI: 10.1096/fj.201902168rr
|View full text |Cite
|
Sign up to set email alerts
|

Bone morphogenetic protein 2 promotes human trophoblast cell invasion and endothelial‐like tube formation through ID1‐mediated upregulation of IGF binding protein‐3

Abstract: Extravillous cytotrophoblasts (EVTs) invade into the uterine wall and remodel spiral arteries for proper placentation. Studies from us and others have demonstrated that the transforming growth factor-β superfamily member bone morphogenetic protein

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 76 publications
(178 reference statements)
6
24
0
Order By: Relevance
“…Several studies have shown that ID1 is a downstream target of BMP, 25‐27 and the administration of IGFBP 3 could reverse the dysregulated expression of vascular and fibroblastic genes in heart tissue with Id conditionally knocked out 28 . Notably, our previous studies also showed that BMP2 promotes cell invasion and endothelial‐like tube formation via the ID1‐mediated upregulation of IGFBP3 expression in human trophoblast cells 11 . Although the essential roles of IGFBP3 induced by BMP2 in trophoblast cell invasion have been confirmed during placentation, 11 there is no evidence showing the functional roles of BMP2‐induced IGFBP3 signaling in the process of endometrial remodeling.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Several studies have shown that ID1 is a downstream target of BMP, 25‐27 and the administration of IGFBP 3 could reverse the dysregulated expression of vascular and fibroblastic genes in heart tissue with Id conditionally knocked out 28 . Notably, our previous studies also showed that BMP2 promotes cell invasion and endothelial‐like tube formation via the ID1‐mediated upregulation of IGFBP3 expression in human trophoblast cells 11 . Although the essential roles of IGFBP3 induced by BMP2 in trophoblast cell invasion have been confirmed during placentation, 11 there is no evidence showing the functional roles of BMP2‐induced IGFBP3 signaling in the process of endometrial remodeling.…”
Section: Introductionmentioning
confidence: 87%
“…Among the BMP subfamily members, BMP2 is expressed in both human secretory endometrial stromal and decidual cells, and this growth factor plays critical roles in regulating the processes of decidualization [7][8][9] and trophoblast cell invasion. [10][11][12] Although numerous BMP subfamily members (BMP2, BMP4, BMP5, BMP6, BMP7, and BMP8) are expressed in the uterus of pregnant mice, only the expression of BMP2 is spatiotemporally correlated with decidualization and embryo implantation. 13 Conditional ablation of Bmp2 in the mouse uterus resulted in complete infertility because the uterine stroma was incapable of undergoing the decidual reaction.…”
Section: Introductionmentioning
confidence: 99%
“…The same group extended these studies and showed that BMP2 promotes TB cell invasion by upregulating N-cadherin via non-canonical ALK2/3/4-SMAD2/3-SMAD4 signaling [78]. They also revealed the role of BMP2 in promoting TB invasion and tube-like formation by ID1-mediated insulin-like growth factor binding protein-3 (IGFBP3) upregulation in primary and HTR8/SVneo cell cultures [47]. Indeed, it is becoming more evident that the TGFβ family uses combinatorial signaling via both SMAD cascades to induce EMT [79].…”
Section: Bmp Cascadementioning
confidence: 86%
“…ID1 is strongly expressed in EVTs of human first trimester placenta compared to CTBs, suggesting that ID1 contributes to the differentiation of CTBs into EVTs [88]. BMP2 promotes TB cell invasion and endothelial-like tube formation by ID1-mediated IGFBP-3 upregulation, as demonstrated both in primary TBs and the HTR8/SVneo TB cell line [47]. ID2 downregulation is essential for CTB differentiation, but in cases of abnormal differentiation from TB in PE women, ID2 expression was constitutive [89].…”
Section: Tgfβ Family-associated Factorsmentioning
confidence: 90%
“…The establishment of trophoblast lineage and differentiation into distinct trophoblast subtypes that exert various functions is tightly regulated by signaling cascades integrating with transcription factor networks 3 . Previous work has identified transcription factor ID1 as a mediator of BMP2‐induced IGFBP3 expression as well as trophoblast invasion and endothelial‐like tube formation 2 . Whether other transcription factors are involved in BMP2‐regulated trophoblast functions and the molecular mechanisms underlying transcriptional regulation of these factors has yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%